Research Progress in Deep Eutectic Solvent Extraction of Bioactive Substances from Animal-derived Processing By-products - BAI Haoxin, XU Weimin, MA Jingjing, GENG Zhiming, ZOU Ye, YANG Biao, YANG Jing, CHENG Mei, YAN Zheng, WANG Daoying, GU Xuedong (Shipin Kexue)
Animal-derived processing by-products are a treasure house of bioactive compounds with huge output and low price. Their efficient exploitation is of great significance. Deep eutectic solvents are a new type of designable “green solvents” and are formed by mixing hydrogen bond donors with hydrogen bond acceptors in appropriate proportions. They possess great advantages, such as easy availability of raw materials, simple preparation, designable structure, and biodegradability and are therefore extensively used in the fields of chemistry, food and medicine. This paper briefly reviews the application of deep eutectic solvents in the extraction of bioactive components from animal-derived processing by-products and gives an outlook on future prospects, hoping to provide new strategies the extraction of bioactive components from animal-derived processing by-products.